Identifikasi Bakteri Agensia Penyebab Motile Aeromonas Pada Ikan Lele Dumbo (Clarias gariepinus) yang Berasal dari Kecamatan Rowosari, Kabupaten Kendal - Apriliyanti, Pramudita; -, Sarjito; Prayitno, Slamet Budi (Journal of Aquaculture Management and Technology, 2013)
Bacterial disease that often affects catfish was Aeromoniasis caused by Aeromonas sp. This disease was considered as an exotic disease since it reslted in mas mortality over 60% within 7 days. The purpose of this study was to determine the clinical signs of fish sample that affected by bacteria. To identifiy the causative agent of bacterial disesase morphological and biochemically, and then to observe the pathogenicity of the selected motile Aeromonas by postulat koch test. The research method used was a combination between exploration and case study. Purposive random sampling was used to collect moribund catfish. Observation of bacterial clinical signs was carried out to 10 moribund catfish that purposively rondomized. Isolation of bacteria from infected skin and kidney were conducted on aeromonas special medium GSP. Purification was done by recultured the selected colony 3 - 5 times on GSP medium. Three (3) selected isolate for Postulate Koch was cultured in Zobelt medium, and then intramusculary injected to 10 tested catfish of 10 - 15 cm, with concentration 108 clinical response and mortality rates were observed every 6 hours for 96 hours. Finally three tested bacteria were identified morphological and biochemically. The results showed clinical signs that clinical signs of moribund catfish related to Aeromonas infection. This could be seen from the presence of haemorrhagic and pethicia of the body skin such as at abdomen, dorsal and tail fins, exopthlamic and gill necrosis. From the 10 catfishes it could be isolates 16 bacterial colonies. Three selceted isolates namely LPK.GSP3.pk, LPK.GSP4.p and LPK.GSP6.k showed their pathogenicity on the postulat koch test. LPK.GSP6.k demonstrated their pathogen caused 35% mortality and 39% moribund, whilst LPK.GSP3.pk and LPK.GSP4.p equally caused 20% mortality and 47% moribund. Morphoogical and biochemical karacterization of the three isolates above indicated that three isolates closely related to Aeromonas caviae, Aeromonas hydrophila and Aeromonas salmonicida. This was might be the reason why these three bacterial isolates quite virulence.